2017
DOI: 10.1186/s40249-016-0220-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of PermaNet® 3.0 and PermaNet® 2.0 nets against laboratory-reared and wild Anopheles gambiae sensu lato populations in northern Tanzania

Abstract: BackgroundMosquitoes have developed resistance against pyrethroids, the only class of insecticides approved for use on long-lasting insecticidal nets (LLINs). The present study sought to evaluate the efficacy of the pyrethroid synergist PermaNet® 3.0 LLIN versus the pyrethroid-only PermaNet® 2.0 LLIN, in an East African hut design in Lower Moshi, northern Tanzania. In this setting, resistance to pyrethroid insecticides has been identified in Anopheles gambiae mosquitoes.MethodsStandard World Health Organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 37 publications
(52 reference statements)
6
27
0
Order By: Relevance
“…Most of these studies used LLINs dating back to 2012 and before, and showed very good bioefficacy of PermaNet® 2.0 [25][26][27][28][29]. In tests conducted in an African setting (Northern Tanzania), PermaNet® 2.0 from 2017 were reported to fulfil all requirements [30]. However in a recent report from Iran, PermaNet® 2.0 did not seem to fulfil bioefficacy requirements [31].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies used LLINs dating back to 2012 and before, and showed very good bioefficacy of PermaNet® 2.0 [25][26][27][28][29]. In tests conducted in an African setting (Northern Tanzania), PermaNet® 2.0 from 2017 were reported to fulfil all requirements [30]. However in a recent report from Iran, PermaNet® 2.0 did not seem to fulfil bioefficacy requirements [31].…”
Section: Discussionmentioning
confidence: 99%
“…The incorporation of a Synergistic effect of Piperonyl Butoxide (PBO) on roof and side panels of LLINs have improved the efficacy of LLINs against resistant mosquitoes [19][20][21][22]. It has a potency of increasing cuticular penetration of insecticides and increase mosquito susceptibility [23].…”
Section: Introductionmentioning
confidence: 99%
“…LLINs with PBO have shown more efficacy against pyrethroid resistant mosquitoes than nets with pyrethroids only [21]. Metabolic resistant is widely spread in malaria vectors across sub-Saharan Africa and PBO could enhance the performance of LLINs by increasing the susceptibility status of the vectors to pyrethroids [21,22]. PBO works by inhibiting the activity of enzymes in insect body [24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations